FAKTOR LINGKUNGAN YANG BERHUBUNGAN DENGAN KEJADIAN PENYAKIT KAKI GAJAH DI DESA KANYURANG KECAMATAN LIUKANG KALMAS KABUPATEN PANGKAJENE DAN KEPULAUAN - Asrijun Juhanto; Miranti Miranti (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
ABSTRACT Filariasis is a contagious disease in a tropical environment caused by filarial worms transmitted by filariasis mosquitoes. Filariasis is also an infectious disease that is still a public health problem because it is spread in most parts of Indonesia. The development of the number of patients with filariasis continues to increase from 2000-2009. Even in some areas have a high level of endemicit. The purpose of this research is to find out how the relationship of environmental factors with the incidence of filariasis in Kanyurang Village, Liukang Kalmas District, Pangakajene Regency, and the Islands This type of research is a quantitative study with cross sectional approach with 70 respondents. Data were analyzed by Chi-Square and presented in tabular form. The variables studied were physical, biological, social and filariasis The results of this study based on statistical tests using the chi-square test found the value of p Physical environment with Filariasis disease occurrence (p = 0,000, Ho Rejected), Biological environment with Filariasis disease occurrence (p = 0.001, Ho Rejected), Social environment with Filariasis disease occurrence (p = 0.00, Ho Rejected), Conclusion There is a relationship between the physical, biological and social environment with the incidence of Filariasis This study suggests that residents pay more attention to the cleanliness of the environment in which they live to reduce the presence of filariasis disease vector breeding places